Effectiveness of restructuring strategies: empirical evidence from Croatian firms - Nenad Filipović; Goran Horvat (Mednarodno Inovativno Poslovanje)
The purpose of the article is to analyze the impact of restructuring actions on the probability of post pre-bankruptcy success. The main research problem is the selection of the most efficient restructuring strategies with the objective of determining which restructuring actions contribute to the probability of successful recovery. Logistic regression model is employed with various specifications added to confirm the robustness of data and results. Research results reveal that financial and managerial restructuring strategies increase the likelihood of success after initiating the pre-bankruptcy. These findings can have practical implications for managers when deliberating on the selection of restructuring strategies, but also to policy makers and regulators when considering the legal framework and other measures for corporate distress resolution mechanism. Contribution of the paper is contained in empirically testing the impact of categorized restructuring strategies on the post pre-bankruptcy success of Croatian firms.